1996
DOI: 10.1073/pnas.93.22.12292
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic coupling between electron and proton transfer in cytochrome c oxidase: simultaneous measurements of conductance and absorbance changes.

Abstract: Bovine heart cytochrome c oxidase is an electron-current driven proton pump. To investigate the mechanism by which this pump operates it is important to study individual electron-and proton-transfer reactions in the enzyme, and key reactions in which they are kinetically and thermodynamically coupled. In this work, we have simultaneously measured absorbance changes associated with electron-transfer reactions and conductance changes associated with protonation reactions following pulsed illumination of the phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
65
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 37 publications
3
65
0
Order By: Relevance
“…Results from earlier studies have shown that the PCET rate is independent of the composition of the buffer or its concentration (17,21), which indicates that buffer molecules do not act as proton donors or acceptors for the protons released through the K pathway. As the observed PCET rate represents the sum of the release and uptake rates, it is not straightforward to calculate a second-order proton-uptake rate constant.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Results from earlier studies have shown that the PCET rate is independent of the composition of the buffer or its concentration (17,21), which indicates that buffer molecules do not act as proton donors or acceptors for the protons released through the K pathway. As the observed PCET rate represents the sum of the release and uptake rates, it is not straightforward to calculate a second-order proton-uptake rate constant.…”
Section: Discussionmentioning
confidence: 96%
“…1) and continues toward the catalytic site via a highly conserved Lys I 362. Proton transfer through this pathway can be studied time resolved upon flash photolysis of a carbon monoxide (CO) ligand from the heme a 3 iron in CytcO in which the catalytic site is reduced while heme a and Cu A are oxidized (15,17) (often referred to as the mixed-valence CytcO). Because the CO ligand stabilizes the reduced state of heme a 3 , after flash photolysis of the complex the electron initially residing at heme a 3 is transferred to heme a over time scales <3 μs (18)(19)(20).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This reaction was originally reported to consist of two phases (5,6): a Ϸ3-s phase of eT between the heme groups was followed by slower electron equilibration with an additional copper site (Cu A ) that lies at the membrane interface in some of the heme-copper oxidases but that is lacking in others (7,8). More recently, it was shown that a third phase of interheme eT (50 s to milliseconds) that is coupled to proton release from the binuclear center can be observed after CO photolysis at high pH (9)(10)(11). However, with the quinol-oxidizing cytochrome bo 3 from Escherichia coli, even more phases were discerned (12).…”
mentioning
confidence: 99%